Nuevas combinaciones en Dipsacaceae. - Devesa Alcaraz, Juan Antonio; Ortega Olivencia, Ana; López Martínez, Josefa (Acta Botanica Malacitana, 2003)
New combinations in Dipsaceae. Palabras clave. Knautia, Lomelosia, taxonomía, Península Ibérica. Key words. Knautia, Lomelosia, taxonomy, Iberian Peninsula.